Developing country stock market immunity during Covid-19 pandemic - Hartono, Hartono (Technium Social Sciences Journal, 2021)
This study aims to examine the empirical research literature on the impact of the Covid-19 pandemic on capital markets in developing countries. In descriptions, research will provide an overview of immunity of the stock market in the face of a pandemic. Starting from the development of the Covid-19 case in developing countries, the impact of the outbreak on stock markets in developing countries, the resilience of developing countries' stock markets compared to developed countries, and the negative/positive impact of government policies to fight Covid-19 on the stock markets of developing countries. This study is a conceptual paper sourced from secondary data published on the theme of the paper and aims to describe the effects of a pandemic that leads to a health crisis on the resilience of a stock market in developing countries. Research papers selected for review were accessed only from high ranking journals. This review is intended to guide future researchers to improve the power of the tests examined.